Twitter sebagai Media Aksi dan Kritik terhadap Pemerintah: Analisis Isi Wacana V. Dijk pada Akun Twitter Aksi Kamisan - Ahsan, Zaka Maulana; Besar, Ibrahim (IAI Nasional Laa Roiba Bogor, 2024)
As a means of sharing ideas and opinions, Twitter is included in the category of social media with active users who have many users, especially in Indonesia, this is what is then used for several parties to convey information messages with certain content, including the @aksikamisan account which is the object of research. to find out what meanings and messages are contained in the Aksi Kamisan Twitter account. Using the content analysis method of van Dijk's model, which divides it into three categories, namely macrostructure, superstructure and, microstructure, this research then results in an answer that the meaning or theme that appears in the text analysis of the Kamisan Action Twitter account is related to the demand for the government to be able to resolve the issue. Previous cases of human rights violations also raised ongoing humanitarian issues by using Twitter as a means of action and criticism of the government to immediately resolve what is demanded of action.